2009
DOI: 10.1094/mpmi-22-9-1143
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carbendazim Resistance on Trichothecene Production and Aggressiveness of Fusarium graminearum

Abstract: Fusarium graminearum (teleomorph, Gibberella zeae) causes head blight of cereals and contaminates grains with trichothecene mycotoxins that are harmful to humans and domesticated animals. Control of Fusarium head blight relies on carbendazim (MBC) in China, but resistance to MBC in F. graminearum is now widespread. Sixty-seven strains were evaluated for trichothecene production in shake culture or in the field. The strains included 60 wild-type strains (30 MBC-resistant and 30 MBC-sensitive), three MBC-resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(82 citation statements)
references
References 30 publications
1
78
0
Order By: Relevance
“…Stephens and colleagues (41) used Affymetrix GeneChips to examine Fusarium gene expression during crown rot of wheat, and reported significant upregulation of Tri5 and Tri14 in planta (compared with mycelial culture). Zhang and colleagues (48) compared Tri5 expression between carbendazin-resistant and -sensitive F. graminearum in shake culture and found higher expression levels in the resistant strain. Gardiner et al (14) showed that Tri5 is strongly expressed in the rachis tissue of wheat, implicating DON in the early spread through the head.…”
mentioning
confidence: 99%
“…Stephens and colleagues (41) used Affymetrix GeneChips to examine Fusarium gene expression during crown rot of wheat, and reported significant upregulation of Tri5 and Tri14 in planta (compared with mycelial culture). Zhang and colleagues (48) compared Tri5 expression between carbendazin-resistant and -sensitive F. graminearum in shake culture and found higher expression levels in the resistant strain. Gardiner et al (14) showed that Tri5 is strongly expressed in the rachis tissue of wheat, implicating DON in the early spread through the head.…”
mentioning
confidence: 99%
“…2). However, there are past reports of resistant strains found in the field (Chen et al 2008;Chen and Zhou 2009) or artificially created via sitedirected mutagenesis of codon 167 in beta-tubulin (Zhang et al 2009b).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the presence of DON was also associated with the higher disease classes. Nevertheless, although this link was apparent, no clear linear correlation was observed between quantitative DON presence and disease symptoms (Audenaert et al, 2009 Some exceptions notwithstanding no real contradictory reports are mentioned although Zhang et al (2009b) and Pirgozliev et al (2002) obtained different results on the effect of azoxystrobin to control F. graminearum and F. culmorum. Possibly, these differences originate from different environmental conditions under which experiments were carried out.…”
Section: The Belgian Situationmentioning
confidence: 97%
“…In addition, a benzimidazole binding site on the β-tubulin gene was suggested to be mutated conferring strains resistant to benzimidazole fungicides such as carbendazim (Qiu et al 2011). An even more interesting observation in carbendazim resistant F. graminearum strains was that a proliferated production of DON was observed (Zhang et al 2009b). …”
Section: Long Term Effectsmentioning
confidence: 99%